Soil Arsenic in Miami-Dade County - Yuncong Li; Ashley Smyth; Jonathan Crane; Christopher Teaf; Guangliang Liu (EDIS)
This new 6-page factsheet provides information about soil arsenic (As) in Miami-Dade County, including basics, background concentrations, cleanup guidelines of soil As, and bioavailability of soil As related to plant and human health. Written by Yuncong Li, Ashley Smyth, Jonathan Crane, Christopher Teaf, and Guangliang Liu, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss696